Comparison Cytological Staining Results of Pleural Effusion with Delayed Time Without Alcohol Fixative and With Alcohol Fixative: PERBANDINGAN HASIL PEWARNAAN SITOLOGI EFUSI PLEURA DENGAN WAKTU TUNDA TANPA FIKSATIF ALKOHOL DAN DENGAN FIKSATIF ALKOHOL - Anggraini, Fransiska; Yohani Mahtuti, Erni (JURNAL BIOSAINS, 2025)
The delay in the examination of pleural effusion fluid may lead to damage to the specimens. To minimize this damage, the addition of fixative solutions is often employed, one of which is 50% alcohol. Therefore, this study aims to determine the effectiveness of using 50% alcohol in fixing smears of pleural effusion fluid that are delayed in examination, as well as to assess the morphological quality of cells in effusion smears stored with and without fixative solutions. The research method is experimental, utilizing a pretest-posttest design. Sampling was conducted using accidental sampling, with specimens categorized into four treatment groups (immediate examination, immediate examination with 50% alcohol fixative, delayed examination without fixative, and delayed examination with 50% alcohol fixative). Smears were stained using the Diff-Quik method. The assessment results were analyzed descriptively and with a paired T-test. In the comparison between immediate without and delayed without, the T-test results showed a significant difference (p = 0.002, <0.05). Conversely, in the comparison between immediate and delayed with fixative, no significant difference was found (p = 0.707, >0.05). The comparison between immediate without and immediate with fixative showed a significant change (p = 0.005, <0.05), while the comparison between delayed without fixative and delayed with fixative was not significant (p = 0.775, >0.05). The alternative hypothesis was rejected based on the paired T-test, as no significant difference was found in the delayed samples compared to the samples that were delayed with the addition of 50% alcohol fixative.